AUCTION FOR THE EXECUTION OF OBJECT OF GUARANTEE OF LIABILITY IN SETTLEMENT OF NON-LOAD LOANS ON HOUSE OWNERSHIP (KPR) - Widya Hastuti (NOMOI Law Review, 2022)
Home Ownership Credit (KPR) is the most chosen alternative provided by many banks, allowing someone to get it with payments in installments, it can even be done in the long term. However, the implementation of credit payments did not proceed in accordance with the credit agreement, namely not making installment payments on loans that had been financed by the plaintiff which was recorded until December 17, 2014 as many as 25.08 installments (25 months or 2 years 1 month) which was then the Defendant I determined the debts of the Plaintiffs as bad loans and by Defendant I (PT BTN (Persero) TBK Bukittinggi Branch it was submitted/through the Bukittinggi State Property and Auction Service Office (KPKNL) (Defendant II) to conduct the auction. The results obtained that the execution of the auction of the object of credit guarantee against housing loans (kpr) which has been filed by the Supreme Court Decision No.128 K/Pdt/2016 can be carried out by the creditor (Bank) which in this case has fulfilled the following steps: stages prior to the auction.